Top feeds can solve the feed problems of sustainable goat production - Barman, K C; Ghosh, M K (Indian Farming, 2015)
Realizing the importance of goat in national economy as well as huge shortage of green roughages for feeding goats in India it becomes utmost important to use top feeds for feeding goats. Goats can be fed exclusively on tree leaves and shrubs because of its superiority over other ruminants in respects of adaptation, digestive efficiency and tolerance of some of the toxic principles present in certain tree leaves.